PENGARUH KEBIJAKAN MARITIM DALAM MENINGKATKAN KUALITAS HASIL TANGKAPAN NELAYAN - Aliya Salsabil Asmin; Annisa Nuraulia Al Qadri S (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Maritime policy plays an important role in monitoring fisheries resources and protecting the natural wealth of fishermen. The research results show that marine strategies that emphasize fisheries asset management, management, marine climate safety, and fishermen training greatly influence the quality of fishermen's catches. Reasonable management of fisheries assets through determining fishing portions and zones preserves the marine environment. In addition, strict supervision in the implementation of fisheries guidelines prevents fishing practices that damage the climate, for example overfishing and fishing using destructive fishing gear. The ocean system also places a high value on working on traits that fishermen acquire through training and teaching. Talented and trained fishermen can increase productivity in catching and handling catches, thereby producing higher quality fishery products. In addition, partners are involved in examining and assessing the implementation of maritime strategies in an organized manner, thereby adding greater transparency and responsibility. The consequences of this exploration underscore the importance of a marine approach in creating a climate that supports fishermen in processing the nature of their catch. By continuing to design and implement possible and planned strategies through government assistance to fishermen, the government can help achieve the goal of improving the quality of fishermen's catches, while maintaining the management of marine assets.